2018
DOI: 10.1002/cepa.849
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of steel slag fines for the production of autoclaved aerated concrete (AAC)

Abstract: Steel slag is a by-product of steel-making processes in which excess lime is often added to remove impurities from liquid steel. Therefore, steel slag is normally rich in calcium compounds, and it thus has the potential for the production of autoclaved aerated concrete (AAC). In this study, a steel slag from the basic oxygen furnace process was examined, and the slag fines (<4 mm) were collected and used as an AAC raw material. The slag fines were divided into four particle size ranges, that is, <0.063 mm, 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To improve the performance of AAC, the solid wastes were added as raw materials to the preparation of the AAC. Siliceous materials (such as ZSM-5 and iron tailing), calcareous materials (steel slag) and sulfate-containing materials (like phosphogypsum and red gypsum) were successfully utilized in the AAC [ 6 , 7 , 8 , 9 , 10 , 11 ]. However, the influence of the high-alkali, sulfate and fluoride-containing materials on the composition and the microstructure of the products in AAC has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of AAC, the solid wastes were added as raw materials to the preparation of the AAC. Siliceous materials (such as ZSM-5 and iron tailing), calcareous materials (steel slag) and sulfate-containing materials (like phosphogypsum and red gypsum) were successfully utilized in the AAC [ 6 , 7 , 8 , 9 , 10 , 11 ]. However, the influence of the high-alkali, sulfate and fluoride-containing materials on the composition and the microstructure of the products in AAC has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, finding alternative raw materials is essential for the preparation of AAC. Many studies have confirmed that industrial waste can be used as feedstock for AAC production, such as graphite tailings, iron ore tailings, blast furnace slag, steel-making slag, waste red gypsum, and zeolites [4,[11][12][13][14][15]. There are also some other types of mining waste which could be utilized within concrete composites of different purposes [16,17].…”
Section: Introductionmentioning
confidence: 99%